Socio-demographic development and burden of mental, substance use disorders, and self-harm: An ecological analysis using the Global Burden of Disease study 2019. (December 2022) - Barbalat, Guillaume; Liu, Sze
Objectives: Whether a country's level of development is associated with an increased or decreased burden of mental and behavioural problems is an important yet unresolved question. Here, we examined the association between the burden of mental and substance use disorders and self-harm with socio-demographic development along temporal and geographical dimensions. Methods: We collected data from the Global Burden of Disease study 2019, which uses robust statistical modelling techniques to calculate disease burden estimates where data are sparse or unavailable. We extracted age-standardized Disability Adjusted Life Year rates as a measure of disease burden for 204 countries and territories, as well as the Socio-Demographic Index, a measure of development reflecting income per capita, fertility rate and level of education. We tested the association between Socio-Demographic Index and Disability Adjusted Life Years for mental and substance use disorders and self-harm, between 1990 and 2019, and across six geographical regions as defined by the World Health Organization. Results: The association between Socio-Demographic Index and Disability Adjusted Life Years was heterogeneous across world regions for all mental and behavioural conditions. For substance use disorders and self-harm, these regional variations were further moderated by time period. Our findings were robust to down-weighing outlier observations, as well as controlling for other socio-demographic variables, and the number of data sources available in each country. Conclusion: Based on data from the Global Burden of Disease study 2019, we demonstrated that the association between mental and substance use disorders and self-harm with socio-demographic development is dependent on geographical regions and temporal periods. This heterogeneity is likely related to geographical and temporal variations in socio-cultural norms, attitudes towards mental problems, as well as health care and social policies. Better knowledge of this spatial and temporal heterogeneity is crucial to ensure that countries do not develop at the expense of a higher burden of mental and behavioural conditions.